Catalytic Cyanation of Aryl halides with Electrophilic N-CN reagent - Dhanalakshmi, Murugan; Anbarasan, Pazhamalai (Synlett)
The palladium catalyzed cyanation of aryl halides has been accomplished for the synthesis of aryl nitriles using electrophilic N-CN reagent as a cyanating reagent. The method utilizes mild base and substoichiometric amount of zinc as promotor and offers mild cyanation that tolerates various functional groups to afford aryl nitriles in good to excellent yields. Preliminary mechanistic investigation revealed the important role of methylene linkage and reductant.